Effect of finishing/polishing techniques and aging on topography, C. albicans adherence, and flexural strength of ultra-translucent zirconia: an in situ study - de Carvalho, Isabelle Helena Gurgel; da Silva, Nathalia Ramos; Vila-Nova, Taciana Emília Leite; de Fatima Dantas de Almeida, Leopoldina; Veríssimo, Aretha Heitor; de Melo, Renata Marques [UNESP]; Zhang, Yu; de Assunção e Souza, Rodrigo Othávio (Springer Nature, 2022)
Objective: To investigate the influence of different finishing/polishing techniques and in situ aging on the flexural strength (σ), surface roughness, and Candida albicans adherence of 5 mol% yttria-stabilized zirconia (ultratranslucent zirconia). Materials and methods: A total of 120 zirconia bars (Prettau Anterior, Zirkonzahn) with dimensions of 8 × 2 × 0.5 mm were divided into 8 groups (n = 15) according to two factors: “in situ aging” (non-aged and aged (A)) and “finishing/polishing” (control (C), diamond rubber polishing (R), coarse grit diamond bur abrasion (B), and coarse grit diamond bur abrasion + diamond rubber polishing (BR)). Half of the samples from each group were subjected to a 60-day in situ aging by fixing the bars into cavities prepared in the posterior region of the base of complete or partial dentures of 15 patients. The samples were then subjected to the mini flexural (σ) test (1 mm/min). A total of 40 zirconia blocks (5 × 5 × 2 mm) were prepared and subjected to roughness (Ra) analyses and fungal adherence and complementary analyses (X-ray diffraction (XRD) and scanning electron microscopy (SEM)). The data of mean σ (MPa) and roughness Ra (μm) were statistically analyzed by two-way and one-way ANOVA, respectively, and Tukey’s test. The Weibull analysis was performed for σ data. The fungal adhesion (Log CFU/mL) data were analyzed by Kruskal–Wallis tests. Results: For flexural resistance, the “finishing/polishing” factor was statistically significant (P = 0.0001); however, the “in situ aging” factor (P = 0.4458) was not significant. The non-aged (507.3 ± 115.7 MPa) and aged (487.6 ± 118.4 MPa) rubber polishing groups exhibited higher mean σ than the other techniques. The non-aged (260.2 ± 43.3 MPa) and aged (270.1 ± 48.8 MPa) bur abrasion groups presented lower σ. The coarse-grit diamond bur abrasion group (1.82 ± 0.61 µm) presented the highest roughness value (P = 0.001). Cell adhesion was not different among groups (P = 0.053). Group B presented the most irregular surface and the highest roughness Ra of 0.61 m. Conclusions: The finishing of ultratranslucent zirconia might be preferably done with a diamond rubber polisher. Moreover, the protocols used did not interfere with Candida albicans adhesion. Clinical relevance: Coarse-grit diamond burs might be avoided for finishing ultratranslucent monolithic zirconia, which might be preferably performed with a diamond rubber polisher.
Keywords: Aging; Biofilm; Dental ceramics; Flexural strength; Polishing; Zirconia